GENE CYP2C19 POLYMORPHISM G681A INFLUENCE ON THE EFFICACY OF CLOPIDOGREL IN ENDOVASCULAR TREATMENT OF ISCHEMIC HEART DISEASE COMORBID WITH TYPE 2 DIABETES - A. N. Repin; T. N. Sergienko; E. F. Muslimova; E. F. Afanasyev (Российский кардиологический журнал, 2015)
Aim. To research on the influence of polymorphism G681A gene CYP2C19 on efficacy of clopidogrel for planned endovascular treatment in stable CHD with second type diabetes.Material and methods. Totally 242 patients included, with chronic CHD, underwent planned angioplastics and stenting of coronary arteries. Of those 79 had 2nd type DM. All patients received double antiplatelet therapy, including acetylsalicylic acid and clopidogrel. For efficacy evaluation, we performed the test of induced platelet aggregation with ADP in 2,5 and 5,0 mcM concentrations after total dose of clopidogrel 300 mg. Genotyping was done with allele-specific polymerase chain reaction with commercial panel “SNP-express” (SPC “LITECH”, Moscow).Results. In our selection, the carriers of allele A differed from homozygous GG with an increased grade of platelet aggregation in ADP stimulation, concentrations 2,5 mcM and 5,0 mcM. While selecting subgroups according to diabetes existence, the mention association was found in non-diabetic group, but not in comorbidity group (CHD and DM). In GG genotype, patients having 2 type DM showed the grade of induced platelet aggregation higher than in carriers of the same genotype without DM. At the same time, allele A carriers without DM did not differ from comorbidity selection in sense of ADP induced response of platelets.Conclusion. So, A allele carriage of G681A polymorphism of gene CYP2C19 is a risk factor for lower clopidogrel efficacy. Diabetes of second type also negatively influences the sensitivity to clopidogrel, but only in GG homozygous.